Descriptions of quadratic plus linear operators which preserve pure states of the quantum system - Saburov, Mansoor (2013)
As we knew, a mathematical formalism of a quantum mechanics says that any quantum system is identified with some finite- or infinite-dimensional Hilbert space; pure states correspond to vectors of norm 1; observables are self-adjoint operators on the space of states. Thus the set of all pure states corresponds to the unit sphere in the Hilbert space [1-2]. It is of interest to describe all linear or nonlinear operators which preserve the pure states of the system. In the linear case, it is nothing more than isometries of Hilbert spaces [1]. In the nonlinear case, this problem was open. In this paper we shall describe all quadratic plus linear operators which preserve pure states of the quantum system.!